2018
DOI: 10.1016/j.jevs.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Glycogen Branching Enzyme Deficiency Mutation in Quarter Horses in Brazil

Abstract: Glycogen branching enzyme deficiency (GBED) is a fatal autosomal inherited disease affecting horses and caused by a nonsense mutation (c.102C>A) in the GBE1 gene. This disease strongly impairs the glycogen metabolism of affected animals resulting in abortion or early death of foals. Although understanding the prevalence of heterozygous for GBED is imperative to estimate the impact of the disease, prevalence studies have yet to be performed in Brazil. The aim of this study was to determine the prevalence of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…As observed for MYH1 , the frequencies of alleles involved in other genetic diseases, that is, PSSM1, 4 HYPP, 10 GBED 13 and hereditary equine regional dermal asthenia (HERDA), 14 in Brazilian QHs were also similar to those found in American QHs 3 . The results obtained in this study and in previous studies 4,10,11,15 suggest that the similarity in the allele frequencies of these mutations may be because Brazilian QHs are often closely related to American QHs 14 and reining is a popular discipline in both countries.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As observed for MYH1 , the frequencies of alleles involved in other genetic diseases, that is, PSSM1, 4 HYPP, 10 GBED 13 and hereditary equine regional dermal asthenia (HERDA), 14 in Brazilian QHs were also similar to those found in American QHs 3 . The results obtained in this study and in previous studies 4,10,11,15 suggest that the similarity in the allele frequencies of these mutations may be because Brazilian QHs are often closely related to American QHs 14 and reining is a popular discipline in both countries.…”
Section: Discussionsupporting
confidence: 82%
“…The foals (foals 1 and 2) and their healthy sires/dams (horses 3‐6) were genotyped for MYHM following the protocols detailed below. In addition, these horses were also genotyped for PSSM1, MH, HYPP and GBED following previously described protocols 4,10,11 . After the death of foal 1, histopathological analysis of semimembranosus, semitendinosus and cardiac muscles was performed with formalin‐fixed paraffin‐embedded tissue stained with haematoxylin and eosin, periodic acid Schiff (PAS) and amylase‐PAS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on prevalence of different diseases with hereditary patterns that affect horses, but no related to hemostasis alterations, have been performed in Brazil: Hereditary equine regional dermal asthenia [17], Hyperkalemic periodic paralysis [18], Type 1 polysaccharide storage myopathy mutation [18], Malignant hyperthermia [19], Glycogen branching enzyme deficiency [20], and Warmblood fragile foal syndrome [21]. Many of these studies demonstrated similar results as found in other countries, such as the USA [16,22].…”
Section: Resultsmentioning
confidence: 99%